Comprehensive interventions for peace: the role of the Social Economy - Marchand Aguilar, José Ricardo (DIXI, 2020)
Objectives: To investigate the role of the Social Economy in comprehensive interventions for peace through the experience in the communities of Tancítaro and Cherán, in Michoacán, Mexico. The construction of peace has been presented, in recent times, as an expression and an honest desire of States, around the world and especially in Latin America, to overcome difficulties and achieve objectives. International organizations insist that solutions must come from structural frameworks, while experience in the field reveals that it is not enough; comprehensive interventions are needed for the impact to be adequate. Methodology: It is a qualitative analysis, typical of a reflection generated around experiences of peace building. Findings: The experiences of cias por la paz, a.c. in the communities of Cherán and Tancítaro show the conse-quences of the interventions of isolated components, as well as the results of those in which the interventions were comprehensive. Conclusions: It is concluded that, when the appropriate processes and methodologies to intervene in a territory are properly implemented, in terms of security and conflict management, it can lead to a decrease in violence. Violence is conceived as only the tip of the iceberg; the product of poorly managed conflicts. This helps point out new approaches to deal with violence beyond the change of base or structure.